Dilema Nilai Budaya Dalihan Na Tolu Pada Pengelolaan Kepegawaian (Studi di Kabupaten Toba Samosir) = Cultural Value Dilema of Dalihan Na Tolu in Officer Management (A Study at Toba Samosir Regency) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The study aims to identify cultural value dilemma in personnel management. The basic thought is that in implementing their task officer or employees having authority to manage employees faced two values, namely, value contained in formal rules and in culture they follow. The problems are (1) is there any cultural value in officer management